Developing a Performance Improvement Model for Fish Processing Units of Small and Medium Enterprises in Indonesia - Heru Suseno; Suadi; Jamhari; Rustadi; Ellia Kristiningrum; Danar Agus Susanto (Jurnal Ilmiah Perikanan dan Kelautan, 2026)
Graphical Abstract   Highlight Research 1. Develops an ecosystem-based model to enhance SME fish processing performance. 2. Applies the Delphi method with multi-sectoral expert consensus. 3. Identifies ten strategic priorities, with certification as the key enabler. 4. Provides a systemic framework aligning institutions, markets, and regulation to improve sustainability and innovation in Indonesia’s fish processing sector.   Abstract This study examines how institutional, market, technological, regulatory, and human capital issues impact the performance of Small and Medium Enterprise Fish Processing Units (SME-FPUs), specifically in Indonesia. The study's goal is to provide an ecosystem-based model for improving the performance of SME-FPUs by combining essential institutional, market, and technology components. Thirteen multi-sectoral experts from government, business, academia, and certification organizations were consulted for the study using the Delphi technique. Strategic variables for model building were identified and prioritized using the expert's insights. Ten strategic priorities were determined by the analysis. These priorities included business licensing facilitation, raw material supply assurance, cold chain infrastructure development, managerial and technical competency capacity building, quality certification promotion, and consumer awareness campaigns. These goals were incorporated into a systemic model that places certification as the primary facilitator in a framework that is favorable to consumers, organizations, and regulations. Study adds to the theoretical conversation by presenting a comprehensive and adaptive ecosystem model that goes beyond reductionist or linear frameworks. In practice, it provides a practical blueprint for governments, development agencies, and industry players to create coherent and sustainable solutions. More study is needed to experimentally evaluate the model's applicability across various geographic settings and sectors of the blue economy.